Duos para vibrafone e piano: estudo interpretativo das peças Sonata para Vibrafone e Piano de Almeida Prado e Domus Aurea de Edmund Campion - Bruno Soares Santos (2010)
The performance techniques of percussion instruments, particularly mallet instruments, have been developing continuously in recent decades. Works and techniques considered difficult to perform, thirty or forty years ago, are now part of the percussionists regular repertoire. In this sense, it is clear that a tradition of notation for these instruments is still a developing process. This research seeks, through the performance and analysis of two works, to enrich the discussion about technique and notation for mallet percussion, specifically the vibraphone. We chose to analyze two duos for vibraphone and piano: Sonata for Piano and Vibraphone by Almeida Prado and Domus Aurea by Edmund Campion. The analysis of these two works offered us a great material for research because they have different types of notation and distinct compositional languages. Thus, they present different challenges for interpretation. The reflection on their performance contributed to the identification of characteristic factors of the vibraphones technique, notation and performance.